2011
DOI: 10.1515/hf.2011.091
|View full text |Cite
|
Sign up to set email alerts
|

Combined bound water and water vapour diffusion of Norway spruce and European beech in and between the principal anatomical directions

Abstract: The combined bound water and water vapour diffusion of wood is of great interest in the field of building physics. Due to swelling stresses, the steady-state-determined diffusion coefficient clearly differs from the unsteady-state-determined diffusion coefficient. In this study, both diffusion coefficients and the water vapour resistance factor of Norway spruce (Picea abies wL.x Karst.) and European beech (Fagus sylvatica L.) were investigated for the principal anatomical directions (radial, tangential and lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…A few experiments have been performed to investigate the water states and diffusion constants in unmodified wood [144]. As the amount of water increases, diffusion of water increases as assessed experimentally using water absorption studies [145][146][147], NMR spin-spin relaxation studies [148], and QENS [149]. The QENS results suggest the presence of at least two distinct water populations in wood, and is able to quantify their dynamic state using a jump diffusion model [149].…”
Section: Water Diffusion and Plasticization In Wood Polymersmentioning
confidence: 99%
“…A few experiments have been performed to investigate the water states and diffusion constants in unmodified wood [144]. As the amount of water increases, diffusion of water increases as assessed experimentally using water absorption studies [145][146][147], NMR spin-spin relaxation studies [148], and QENS [149]. The QENS results suggest the presence of at least two distinct water populations in wood, and is able to quantify their dynamic state using a jump diffusion model [149].…”
Section: Water Diffusion and Plasticization In Wood Polymersmentioning
confidence: 99%
“…These differences can be partially explained by the different densities of the radial and tangential specimens and partially due to the different thermal conductivity of wood in the radial and tangential directions (λ R > λ T ). These differences can be attributed to the significant number of wood rays in hardwoods and their orientation [28,29]. In addition, in the tangential section reasonably the ratio of earlywood and latewood is different, depending by the position if close to the pith or far from the pith [3].…”
Section: Resultsmentioning
confidence: 99%
“…Heat treatment of beech blocks were performed by Hakkou et al (2005) in France, in a reactor placed in an oven, the wood surface started to be hydrophobic (CA > 90°) after 120 °C [21]. CA characterized on heat-treated beech wood at 240 °C in an industrial oven showed that the variation after and before processing (∆θa = 16.2°) was low compared with other species (spruce = 44.7°, pine = 62.4° poplar = 85.8°) [28]. The value of ∆θa for beech processed by contact heating for radial specimens (∆θa = 200/20R-REFR) was 24.0° and 5.6° for tangential (∆θa = 200/20T-REFT).…”
Section: Resultsmentioning
confidence: 99%
“…The diffusion coeffi cient and Biot number, evaluated from adsorption experiment of beech wood in humid air are random variables (Comstock, 1963;Dekrét and Kurjatko, 1986;Hrčka, 2008;Sonderegger et al, 2011). The critical p-level value was set to 5 % as a variability of data can be assumed.…”
Section: Rezultati I Raspravamentioning
confidence: 99%